The Orosirian-Statherian banded iron formation-bearing sequences of the southern border of the Espinhaço Range, Southeast Brazil - Rolim, V.; Rosière, C.; Santos, J.; McNaughton, Neal (2016)
The Serra da Serpentina and the Serra de São José groups are two distinct banded iron formation-bearing metasedimentary sequences along the eastern border of the southern Espinhaço Range that were deposited on the boundary between the Orosirian and Statherian periods.The Serra da Serpentina Group (SSG) has an Orosirian maximum depositional age (youngest detrital zircon grain age = 1990 ± 16 Ma) and consists of fine clastic metasediments at the base and chemical sediments, including banded iron formations (BIFs), on the top, corresponding to the Meloso and Serra do Sapo formations, respectively, and correlating with the pre-Espinhaço Costa Sena Group. The SSG represents sedimentary deposition on an epicontinental-epeiric, slow downwarping sag basin with little tectonic activity.The younger Serra de São José Group (SJG) is separated from the older SSG by an erosional unconformity and was deposited in a tectonically active continental rift-basin in the early stages of the opening of the Espinhaço Trough. The Serra do São José sediments stretch along the north-south axis of the rift and comprise a complete cycle of transgressive sedimentary deposits, which were subdivided, from base to top, into the Lapão, Itapanhoacanga, Jacém and Canjica formations. The Itapanhoacanga Formation has a maximum depositional age of 1666 ± 32 Ma (Statherian), which coincides with the maximum depositional age (i.e., 1683 ± 11 Ma) of the São João da Chapada Formation, one of the Espinhaço Supergroup's basal units. The Serra de São José Rift and the Espinhaço Rift likely represent the same system, with basal units that are facies variations of the same sequence.The supracrustal rocks have undergone two stages of deformation during the west-verging Brasiliano orogeny that affected the eastern margin of the São Francisco Craton and generated a regional-scale, foreland N-S trending fold-thrust belt, which partially involved the crystalline basement. Thrust faults have segmented the terrain into a large number of tectonic blocks, where the stratigraphic sequence was nevertheless well preserved.